Pengaruh perubahan sirkulasi terhadap fungsi ruang di rumah Peranakan, Kampung Babagan, Lasem - Tessa Eka Darmayanti; Azizi Bahauddin (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Effects of changes in circulation on spatial function in peranakan house, Babagan Village, Lasem A change could affect circulation in a building. The change may be influenced by external or internal sources that are related to the perspective of tradition, culture and social surroundings. It may indirectly presents a new feature that can accommodate the needs of residents and this happens in one of the Peranakan houses in Lasem. It could be seen as a form of conservation while respecting family and social traditions and culture. The purpose of this study is to understand which components that influence changes in the circulation of space within the Peranakan-Kidang Mas housing complex which includes the main building, courtyard, kitchen, and workshop. To answer these objectives, the methods used are surveys, interviews, and observation. This narrative research discussion is supported by a spatial concept and research findings show that changes in circulation make it possible to give new meaning to the function of a space. © 2020 Tessa Eka Darmayanti, Azizi Bahauddin